Vitalizing logistics strategies for Tiksi Port using the interpretive structural modelling method - Margarita Krivoshapkina; Young-Seo Choi; Maria Listan Bernal; Gi-Tae Yeo (Asian Journal of Shipping and Logistics, 2024)
Tiksi Port is a Russian seaport located on the Laptev Sea shore in the Central Arctic region and holds potential as a crucial and versatile hub for the improvement of the Eastern Arctic sector. It is one of the main ports on the Northern Sea Route and can potentially become the primary point for transporting various types of cargo. Currently, Tiksi Port is shallow and incapable of receiving large sea vessels and although it was initially equipped with handling equipment, signs of decline are visible. This study aims to identify the critical logistics elements of Tiksi Port and classify them according to their level of significance in vitalizing the logistics activities of the port for further practical use. Interpretive Structural Modelling and the Matrix of Cross Impacts Multiplication Applied to a Classification (MICMAC) method was used in this study. The study findings revealed ten factors that appeared at three levels of importance. According to the analysis results, “combating oil spills” was present at Level 3, which is the first and most fundamental level to be improved. Tiksi Port officials and government ministries can use these results as a reference for development and to support the establishment of a cost-effective and agile logistics system for related companies.